Determinación de la relación de células epiteliales vaginales ante-mortem y calidad de ovocitos post-mortem en bovinos introducidos en el Camal Municipal de Babahoyo. - Anchundia Huacon, Marlys Fernanda (2016)
SUMMARY The research was carried out in the city of Babahoyo in the province of the Rios the purpose of determining the relationship of vaginal epithelial cells and the quality intrinsic of immature oocytes bovine females in the municipal slaughterhouse of Babahoyo. Was collected 200 samples of vaginal cytology and 400 ovaries of 200 female cattle.The determination of cells and top charts of oocytes were carried out in the laboratory of the Faculty of Sciences Agricultural of the University Technique of Babahoyo. Commit that 126 non-pregnant females (64 %) and of 74 pregnant (37 %) animals in which it was found that a total of 2331 oocytes.Of non-pregnant females It was determined that there is a of viable oocytes and 33 % of non-viable oocytes by determining the upper percentages 74 % of cells corniified who are whit the animal manifested in its estrous cycle the zeal. In the pregnant animals (37%) of animals sampled was identified 58 % of oocytes viable and 42 % of no - viable oocytes with a 34 % of cells epithelial cornfied, cells were higher than the other vaginal epithelial cells found. Determining that there is a relation between the percentages of cells cornified and the viable oocytes in females bovines as found higher percentages of cells cornified that the other epithelial cells and the percentages of viable oocytes were acceptable and higher than those of non-viable oocytes in non-pregnant females.